Protocol for a qualitative study exploring the perception of need, importance and acceptability of a digital diabetes prevention intervention for women with gestational diabetes mellitus during and after pregnancy in Malaysia (Explore-MYGODDESS) - Siew Mooi Ching; Kimberley Goldsmith; Nicola Guess; Iliatha Papachristou Nadal; Helen Murphy; Barakatun Nisak Mohd Yusof; Irmi Zarina Ismail; Hanifatiyah Ali; Angus Forbes; Nur Hafizah Mahamad Sobri; Faezah Hassan; Nurul Iftida Basri; et al. (BMJ Open)
Introduction Women who develop gestational diabetes mellitus (GDM) have an increased risk of developing type 2 diabetes, and to reduce this risk the women have to adopt healthy behaviour changes. Although previous studies have explored the challenges and facilitators to initiate behaviour change among women with GDM, there is limited data from Malaysian women. Thus, this study will explore the factors affecting the uptake of healthy behaviour changes and the use of digital technology among women and their healthcare providers (HCPs) to support healthy behaviour changes in women with GDM.Methods and analysis The study will be modelled according to the Capability, Opportunity, Motivation and Behaviour and Behaviour Change Wheel techniques, and use the DoTTI framework to identify needs, solutions and testing of a preliminary mobile app, respectively. In phase 1 (design and development), a focus group discussion (FGDs) of 5–8 individuals will be conducted with an estimated 60 women with GDM and 40 HCPs (doctors, dietitians and nurses). Synthesised data from the FGDs will then be combined with content from an expert committee to inform the development of the mobile app. In phase 2 (testing of early iterations), a preview of the mobile app will undergo alpha testing among the team members and the app developers, and beta testing among 30 women with GDM or with a history of GDM, and 15 HCPs using semi-structured interviews. The outcome will enable us to optimise an intervention using the mobile app as a diabetes prevention intervention which will then be evaluated in a randomised controlled trial.Ethics and dissemination The project has been approved by the Malaysia Research Ethics Committee. Informed consent will be obtained from all participants. Outcomes will be presented at both local and international conferences and submitted for publications in peer-reviewed journals.